A Patient-Centered Integrative Approach Improves Visual Field Defect: A Case Report. (May 2021) - Kao, Lan; Hui, Ka-Kit; Hui, Edward
We present a case involving a patient with a complicated visual field defect preventing her from renewing her driver license. It highlights the underappreciated role of chronic stress in the genesis and perpetuation of ill health and the potential of Chinese medicine (CM) to complement biomedicine in the treatment of an intractable visual disorder. The patient experienced impaired vision from age 15, and ophthalmologists considered various diagnoses including optic neuritis and acute zonal occult outer retinopathy (AZOOR)-complex disorder with acute macular neuroretinopathy. She was treated with an integrative East-West medical approach incorporating acupuncture, cupping, trigger point injections, guidance on self-care and lifestyle modification. Although the eye disorder was not cured, there was visual improvement as demonstrated by various objective ophthalmologic tests, and the patient was able to renew her driver license. Visual improvement remained stable upon follow-up examination three years after the treatment intervention. Other concomitant health issues reported by the patient also improved including amelioration of neck pain, a more regular menstrual cycle, and decreased anxiety. This case demonstrates how a patient with an intractable complex eye disorder can have objective visual improvement when treated with an integrative patient-centered approach.